An on-line decision support system for retail chain store / Fadi Moh’d Salim Shrouf - Fadi Moh’d , Salim Shrouf (2006)
In recent times, online retail stores have become more popular and the global retailing trend is moving towards chain stores that provide a wider assortment of products and e-service e.g. online purchasing. However, online retail chain stores face many problems and limitations pertaining to the delivery of the online orders and in the management of stores in the retail chain stores. This research suggests a solution for these limitations, whereby an online decision support system for retail chain stores is developed to overcome these problems. The system can be used to help managers by generating reports to help them in making decision on how to manage the stores in a more efficient way. In overcome the problem pertaining to delivery of the online orders by a customers, the system is able to find a near subset of stores, based on the customer’s postal/zip code, and make a decision as to which store should deliver the customer's order depending on the lowest cost of delivery. In addition to this, if an item in the customer's order is not available in the selected store, the system will select the next “best” store based on the next lowest cost of delivery to fulfill and deliver the item to the customer. The system is also able to manage the product inventory for each store in the retail chain stores. Furthermore, the system can help customers to purchase items online in a convenient way.